The meanings of work and masculinity: a study with military police officers (Research, Society and Development, 2021)
The research aims analyze the meanings of work for military police officers and the meanings’ associations with the concepts of masculinity. Based on quantitative research, three hundred Brazilian military police responded to a structured questionnaire classified on a five-point Likert scale. Data was collected in person and online using Qualtrics software, then tabulated and organized using JASP v software. 0.14.1. The results shows that military police officers perceive recognition of their work, based on autonomy. Moreover, they see their work as strongly related to moral rectitude and social utility. They associate the meanings of their work with issues of dignity and respect for human rights and the feeling of generating positive impacts and results for society. However, this also results in a homogenization of the individual within the organization: they cannot show emotions, must be heterosexual, withstand provocations, be conservative in terms of the values of the institution and the profession.